2007
DOI: 10.1007/s11064-006-9214-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maintenance Electroshock on the Oxidative Damage Parameters in the Rat Brain

Abstract: Although several advances have occurred over the past 20 years concerning refining the use and administration of electroconvulsive therapy to minimize side effects of this treatment, little progress has been made in understanding the mechanisms underlying its therapeutic or adverse effects. This work was performed in order to determine the level of oxidative damage at different times after the maintenance electroconvulsive shock (ECS). Male Wistar rats (250-300 g) received a protocol mimicking therapeutic of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…The brain is particularly vulnerable to oxidative stress because of its high rate of oxygen consumption, high level of transition metal, and polyunsaturated fatty acids. Our results did not demonstrate a more vulnerable region to the occurrence of oxidative damage, as we demonstrated that to other disease there is a different pattern of oxidative damage in several brain structures [27][28][29][30]. Oxidative damage contributes to mitochondrial dysfunction leading to energy failure.…”
Section: Discussioncontrasting
confidence: 49%
“…The brain is particularly vulnerable to oxidative stress because of its high rate of oxygen consumption, high level of transition metal, and polyunsaturated fatty acids. Our results did not demonstrate a more vulnerable region to the occurrence of oxidative damage, as we demonstrated that to other disease there is a different pattern of oxidative damage in several brain structures [27][28][29][30]. Oxidative damage contributes to mitochondrial dysfunction leading to energy failure.…”
Section: Discussioncontrasting
confidence: 49%
“…These effects are characterized by increases in neurotrophic factors and other molecules, enhancing the survival and proliferation of neuronal cells and inhibiting apoptotic signals [26,50]. Published findings regarding oxidative stress differ considerably: [40,51] Jornada et al (2007) found that electroconvulsive therapy in mice prompted an increase in neurotrophic factors together with minimal oxidative damage in brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Feier et al (4) found a delayed increase in oxidative damage after ECS and a decrease in SOD and CAT activities in hippocampus and striatum in rats. Jornada et al [12] reported no alteration in the lipid peroxidation and no protein damage in the hippocampus, cortex, cerebellum, and striatum immediately after, 48 h and 7 days after the last maintenance ECS. Zupan et al (19) found oxidative lipid damage only in the frontal cortex, but not in the hippocampus, cerebellum, and the pons/medulla region in their experimental animal conditions.…”
Section: Discussionmentioning
confidence: 97%
“…While some researchers found an increase (4) in oxidants, others measured a decrease (11); meanwhile, Jornada et al [12] reported no significant changes in oxidative metabolites after ECS. Regarding antioxidants, Erakovic et al (10) and Feier et al [4] measured a decrease, but Baricello et al (11) found an increase.…”
Section: Introductionmentioning
confidence: 97%